Research on tourism industrial cluster and information platform based on Internet of things technology - Xue Li (International Journal of Distributed Sensor Networks)
With the continuous development of Internet of things technology, the tourism industry cluster based on the Internet of things platform has gradually formed, and the resource integration mechanism of industrial clusters under the Internet of things platform has gradually become a research hotspot. Starting from the theory of niche research in tourism industry cluster, this article improves the mode of industrial clusters through the Internet of things platform. Then, combining resource integration game model, the resource integration mechanism of Internet of things tourism industry cluster is formed. Relying on the information management model of the Internet of things industry, the information platform of industrial clusters is constructed, and the simulation research is carried out by MATLAB. The results show that the overall industrial income generated by the resource allocation mechanism under the Internet of things platform is better than that under the traditional resource allocation mechanism, and the resources integration of tourism industry cluster under the Internet of things platform is achieved, which provides a theoretical basis.